Estrogenic Activity and Endocrine Disruptor Compounds Determined in Guanabara Bay (Brazil) by Yeast Estrogen Screen Assays and Chemical Analyses - Nascimento, Marilia Teresa Lima do; Santos, Ana Dalva de Oliveira; Cunha, Danieli Lima da; Felix, Louise Cruz; Gomes, Giselle; Hauser-Davis, Rachel Ann; Fonseca, Estefan Monteiro da; Bila, Daniele Maia; Baptista Neto, José Antônio (Anuário do Instituto de Geociências, 2022)
Studies assessing the presence of endocrine disrupting compounds in marine environments have increased in the last decades. In Brazil, the combination of poor sanitation conditions and low investment in sewage treatment plants leads to significant contamination of receiving waters. The risks of these micropollutants in the aquatic biota include biochemical and histopathological alterations of the liver, gonads, and kidneys, as well as, reproductive process and development modifications, and behavioral changes, among others. The aim of this study was to evaluate the quality of the surface and deep waters of Guanabara Bay, southeastern Brazil, regarding the presence of estrogenic substances. Acute toxicity assays were also conducted employing Vibrio fischeri. The estrogenic activity of the water samples was determined by Yeast Estrogen Screen assay and the quantification of the Bisphenol A, estriol, 17β-estradiol, and 17α-ethinylestradiol by high-performance liquid chromatography, using fluorescence and diode array detectors. Estrogenic activity ranged from 9 to 77 ng L-1 of estradiol equivalents. The highest micropollutants concentrations were detected for bisphenol A (298.5 and 465.5 ng L-1), followed by 17α-ethinylestradiol (248 and 256.9 ng L-1), estriol (70.7 and 179.6 ng L-1), and 17β-estradiol (167 and 174.8 ng L-1) for surface and deep waters, respectively. The findings indicate significant risks for the Guanabara Bay ecosystem. No acute toxicity effects were observed in the V. fisheri assay. These data reflect the current environmental degradation situation of the bay’s waters and highlight the need for the systematic monitoring of this important estuary.